IMPLEMENTATION OF DISCOVERY LEARNING METHODS TO INCREASE ACTIVITY AND LEARNING RESULTS IN BANYUAJUH 2 ELEMENTARY SCHOOL - Rofilah Rohadatul Aisy; Rika Wulandari; Kusnaningsih Kusnaningsih (Citra Dharma Cindekia, 2022)
This study aims to increase the activeness and competence of students in Indonesian class IV subjects at Banyuajuh 2 elementary school through the application of discovery learning methods. This research is a Classroom Action Research (CAR) with the Kemmis and Mc Taggart model which was carried out in two research cycles. The subjects of this study were the fourth grade students of elementary school Banyuajuh 2 for the 2022/2023 academic year, totaling 25 students. Data collection techniques in this study used observation for the implementation of learning and student activity, tests for cognitive competence, and documentation. The success indicator of this research is more than 70% activeness of students and 75% of students reach KKM of 76. The results show that through the application of the Discovery Learning learning method can increase student activity and competence in Indonesian subjects. This can be seen from: (1) an increase in student activity in each cycle. The activeness of students in the first cycle was 31.29%, and the second cycle was 71.83%; (2) an increase in class average and student learning completeness. The average class in the first cycle is 75.74, and the second cycle is 87.33. Students' learning mastery as measured by cognitive competency tests in the first cycle was 60%, and the second cycle was 92%.